Intergroup Variation of Social Relationships in Wild Vervet Monkeys: A Dynamic Network Approach - Borgeaud, Christèle; Sosa, Sebastian; Bshary, Redouan; Sueur, Cédric; van de Waal, Erica (Frontiers in Psychology, 2016)
Social network analysis is a powerful tool that enables us to describe and quantify relationships between individuals. So far most of the studies rely on the analyses of various network snapshots, but do not capture changes over time. Here we use a stochastic actor-oriented model (SAOM) to test both the structure and the dynamics of relationships of three groups of wild vervet monkeys. We found that triadic closure (i.e. the friend of a friend is a friend) was significant in all three groups while degree popularity (i.e. the willingness to associate with individuals with high degree of connections) was significant in only two groups (AK, BD). The structure and dynamics of relationships according to the attributes of sex, matrilineand age differed significantly among groups. With respect to the structure, when analyzing the likelihood of bonds according to the different attributes, we found that individuals associate themselves preferably to individuals of the same sex only in two groups (AK, NH), while significant results for attachment to individuals of the same matriline were found also in two groups (BD, NH). With respect to the dynamics, i.e. how quickly relationships are modified, we found in two groups (AK, BD) that females’ relationships were more prone to variation than males’. In the BD group, relationships within high-ranking matrilines were less stable than low-ranking ones while in the NH group, juveniles’ relationships were also less stable than adults’ ones. The intergroup variation indicates that establishing species-specific or even population specific characteristics of social networks for later between-species comparisons will be challenging. Although, such variation could also indicate some methodological issue, we are quite confident that data was collected similarly within the different groups. Our study therefore provides a potential new method to quantify social complexity according to natural demographic variation.